The Effect of Slow Stroke Back Massage (SSBM) on Breast Milk Production in Postpartum Mothers on Days 3–5 - Ghina Nada Maghfira; Sugijati; Susilawati (Indonesian Journal Publisher, 2026)
Background: Suboptimal breast milk expression in postpartum mothers remains a challenge in achieving exclusive breastfeeding, particularly in Kaliwates District, where the coverage is only 17.9%. Six out of ten postpartum mothers in the Puskesmas Kaliwates working area reported poor milk flow during the first week after delivery. Complementary therapies such as Slow Stroke Back Massage (SSBM) is a gentle, rhythmic massage technique applied from the upper to lower back, aimed at stimulating the release of oxytocin and endorphins, both of which play crucial roles in lactation. Purpose: This study aims to determine the effect of SSBM on breast milk expression in postpartum mothers on day 3–5 in the working area of Puskesmas Kaliwates. Methods: This research was conducted quantitatively using a one-group pretest-posttest design with a total sample of 23 respondents. Data were collected via questionnaires and analyzed using the Wilcoxon Signed-Rank Test. Results: Before the intervention, most respondents had smooth (60.9%) and poor (34.8%) milk output. After the intervention, most respondents experienced improvement, with 60.9% showing very smooth milk output and 30.4% showing smooth milk output. The analysis showed a significance value of 0.0000 (p<0.05), indicating a significant effect of SSBM on breast milk expression. Conclusion: SSBM can effectively improve breast milk expression in postpartum mothers on days 3–5 in the Puskesmas Kaliwates area in 2025.